2013
DOI: 10.1902/jop.2012.110757
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliative Cytology and Titanium Dental Implants: A Pilot Study

Abstract: Regardless of an inflammatory response, ions/particles are released from the surface of the implant into the biologic milieu. Exfoliative cytology is a simple technique that may be used to detect metal particles in cells exfoliated from the peri-implant mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 25 publications
7
121
3
2
Order By: Relevance
“…Previous studies have shown the presence of titanium particles in peri‐implant tissues; however, no statistical evidence of an association between dissolved titanium and peri‐implantitis has been reported. Titanium particles have been found in epithelial cells exfoliated from peri‐implant tissues, 20 foreign bodies consisting of titanium and cement have been found in soft tissue of implants with peri‐implantitis, 19 and titanium elements have been found in bone and soft tissue biopsies retrieved from sites with peri‐implantitis 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown the presence of titanium particles in peri‐implant tissues; however, no statistical evidence of an association between dissolved titanium and peri‐implantitis has been reported. Titanium particles have been found in epithelial cells exfoliated from peri‐implant tissues, 20 foreign bodies consisting of titanium and cement have been found in soft tissue of implants with peri‐implantitis, 19 and titanium elements have been found in bone and soft tissue biopsies retrieved from sites with peri‐implantitis 18 …”
Section: Discussionmentioning
confidence: 99%
“…Sample size estimation was performed based on previously published results by Olmedo et al 20 who assessed levels of titanium particles by ICP‐MS in pooled samples from epithelial cells around implants with peri‐implantitis compared with healthy implants. Based on the effect size observed, twenty implants per group were deemed adequate in the present study to yield 90% power to detect a significant difference between groups using a test of means at α = 0.05 and accounting for 30% attrition due to sampling/assay errors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coli et al 69 pointed out that probing depths of more than 4 mm cannot be seen as a sign of pathology around oral implants and an increase in probing depths values over time need not automatically be associated with loss of supporting bone around oral implants. 80 One important aspect that has not been debated in the literature and that has not yet been properly tested is the fact that probing around oral implants could potentially result in trauma to the periimplant soft tissues leading to inflammation, apical proliferation of the epithelium, and consequent bone loss, particularly as it seems like true probing forces and pressures are higher than suggested values from the literature. Released titanium particles may act as additional foreign bodies initiating the release of inflammatory mediators associated with bone resorption 70-78 as already described in the case of orthopedic implants.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…Prior to surgery, cytology samples from the buccal marginal gingiva and junctional epithelium (JE) at the level of implant-abutment interface area were collected using a microbrush (regular size 2.0 mm) and smeared onto a glass slide following the protocol established by Olmedo et al (2013) 13 .…”
Section: Specimen Preparation (Exfoliative Cytology and Histology)mentioning
confidence: 99%